Elite directors, London finance, and British overseas expansion: Victorian railway networks, 1860–1900. (4th December 2020) - Amini, Shima; Toms, Steven
Abstract: This article considers how international economic expansion impacts on the composition of elite groups on boards of companies. We examine, why, at the height of the British Empire, boards of national, imperial, and international railway companies, financed from London, were dominated by elites drawn differentially from the aristocracy, the military, finance, and politics. To investigate the reasons for these differences, we conduct a social network analysis of railway company boards in three countries during the second half of the nineteenth century. Results reveal that aristocratic directors were dominant in Britain, military directors in India, and financier directors in Argentina, suggesting that their influence drew on local knowledge, resource access, and network connections. They did not serve on boards for merely ornamental purposes.